Wordwall Quiz Assessment on Global Warming Impacts on Student Learning Activities and Outcomes - Hanim Isti Fadah; Ike Lusi Meilina; Bambang Supriadi (Universitas Lambung Mangkurat, 2026)
Physics learning is a learning process that contains elements of interest and involves scientific information and the environment. The application of the Wordwall quiz assessment on the subject of global warming in class X-1 students at SMA Negeri 5 Jember has the objectives of (1) increasing student learning activities after applying the Wordwall quiz assessment and (2) improving student learning outcomes after applying the Wordwall quiz assessment. The type of research used is classroom action research with the Kemmis and McTaggart model. The research subjects were X-1 class students with a total of 36 people. Data collection techniques used questionnaires, tests, interviews, observations, and documentation. Data on student learning activities in cycle I obtained an average value of 72.86. Based on the results in cycle I, improvements were made in cycle II with an average student score of 75.39. Data on student learning outcomes in cycle I obtained a percentage of 58%. The learning outcomes obtained in cycle II were 94%. Based on the results of the study, it was found that the activity and learning outcomes of students increased with the application of the Wordwall quiz assessment in the classroom. The implication of this study is that the use of the Quiz Wordwall assessment on the topic of global warming can increase student engagement, which has a positive impact on their learning activities and outcomes. This supports the integration of interactive technology in the science learning process.